Visual guidance of an on-orbit free-floating manipulator using a mobile camera - Ramón, José Luis; Pomares, Jorge; Felicetti, Leonard (Springer, 2022)
A direct visual-servoing algorithm for control a space-based manipulator is proposed. A two-arm manipulator is assumed as a baseline scenario for this investigation, with one of the arms performing the manipulation and the second arm dedicated to the observation of the target zone of manipulation. The algorithm relies on images taken independently from de-localized cameras, e.g. at the end-effector of a second manipulator. Through the implementation of a Kalman filter, the algorithm can estimate the movements of the features in the image plane due to the relative movements between the camera and the target and then calculate the torques to be provided to the joints of the manipulator by adopting a visual servoing control strategy. Simulations results in two different scenarios have been presented to show an adequate behaviour of the presented approach in on-orbit-servicing operations.
Keywords: Space robotics; On-Orbit servicing; Visual servoing; Impedance control